Co-innovation and scaling: Local Technical Agroclimatic Committees - Castellanos, Andrea Estefania; Quintero, Diana Katherine; Lizarazo, Miguel; Martínez Barón, Deissy (2023)
This document is an integral part of a more extensive report that conducts a systematic review of various cases addressing participatory co-innovation models and approaches in the agri-food systems of Latin America and the Caribbean. The CGIAR's AgriLAC Resiliente initiative, especially its scaling component, aims to thoroughly analyze the co-innovation and scaling processes of these cases to identify and examine lessons learned, key enabling factors, and leverage points that trigger the scaling of agricultural innovations in specific contexts. Additionally, it seeks to provide information to guide the design of scaling strategies for innovations developed by the AgriLAC Resiliente initiative. To achieve this purpose, a synthesis of the Local Technical Agroclimatic Committees (MTA in Spanish) case is presented, analyzing essential elements of both the co-creation and scaling processes in the region.